Re-approaching interview data through qualitative secondary analysis: interviews with internet gamblers. Issue 5 (2nd September 2020) - Hughes, Kahryn; Hughes, Jason; Tarrant, Anna
ABSTRACT: This paper addresses two interrelated questions concerning what interview data are and how researchers might use them. The first considers the value of a shift from a predominant or exclusive focus upon how data are constructed and produced at interview, and towards how such data might be apprehended through different forms of engagement. The second question relates to how and what qualitative secondary analysis (QSA) might be used to tell about the social world. In exploring this, we advance a critique of the divide between primary and secondary analysis, recasting the debate in terms of different degrees and qualities of 'proximity' and 'distance' from the formative contexts of data generation, and the distinctive analytical affordances that relate to these. Using QSA of interview data from a study of problem internet gambling as an empirical crucible, we consider the kinds of participation that interviewees develop through reciprocal engagement with interviewers. We illustrate how participants reflexively negotiate the affordances and limits to the narratives through which they frame and recount their experiences. Finally, we show how interview data can be used both to speak of the temporal, relational, spatial, epistemic contexts of their production, and also to contexts and questions beyond these.